Eradication of Societal Poverty: Adult Education and Non-Formal Education as a Steady Alternative in Alabata Community Area of Akinyele LGA, Oyo State (Unilorin Journal of Lifelong Education, 2025)
This study examined eradication of societal poverty: Adult education and Non-Formal Education as a steady alternative in Alabata Community Area in Akinyele LGA, Oyo State. This study adopted survey research design. The target population for the study consisted all the dwellers in Alabata Community in Akinyele Local Government Area of Oyo State. Ten area were selected. In each area, 12 people were selected through simple random sampling. A total of 120 respondents were sampled for the study. For the purpose of data collection, instrument titled “Eradication of Poverty and Adult Education Questionnaire, (EPAEQ) was used to elicit data. Validity the instrument was done by experts in Adult Education. A test-retest method was used to administer the instrument (with an interval of two weeks) on 6 dwellers (in one area) who were not part of the study. Three research questions were answered using simple percentage. The findings revealed that the basic causes of poverty in Alabata community were found to be high rate of youth unemployment, poor agricultural production as a result of poor weather condition, high level of illiteracy, large family size (Polygamous) and poor government economic policies has caused poverty. Also, untimely death among the inhabitants especially children, high rate of crime among the youth, high rate of unemployment especially among the youth and slow rate of community development exist as a result of poverty. More so, Adult Education as an option can eradicate poverty in Alabata Community. It was found that Adult education as an option provides nationwide mass literacy campaign, Adult education creates better living for the community, Adult education supports public private partnership in the community, Adult education supports IT and other infrastructural facilities and that Adult education provides remedial and life-long education for youths and adults. Recommendation were made that there is need for Adult education and Non-Formal Education programmes to be widely pronounced into coherent and purposeful strategy in the pursuit of a relatively development mission; economic planners need to be coherent in the planning of programmes of adult education and policies and that quality education should be provided by the state government in the area particularly for the youth who are passing through abject poverty.